Compatibility of pellet fuelling with ELM suppression by RMPs in the ASDEX Upgrade tokamak. (17th April 2020) - Valovič, M.; Lang, P.T.; Kirk, A.; Suttrop, W.; Bock, A.; McCarthy, P.J.; Faitsch, M.; Plöckl, B.
Abstract: It is demonstrated that tokamak plasma can be fuelled by pellets while simultaneously maintaining ELM suppression by external resonant magnetic perturbations (RMPs). Pellets are injected vertically from high field site and deposited at outer part of plasma cross section. Each pellet triggers a benign MHD event followed by a short lived ELM-free phase. The ELM suppression phase with pellet fuelling lasts 11 pellet cycles and is terminated by intentionally increasing the pellet rate to cause a transition to the ELMy phase.